Value Clarification Technique (VCT) Untuk Meningkatkan Perilaku Respect Mahasiswa - Navion, Febranti Putri (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
The current phenomenon shows that students tend to be unable to accept differences, work with different groups, and appreciate diversity. However, in their activities as students and members of society, students need to exhibit respect as a fundamental behavior for interacting with their environment. This study aims to determine the effectiveness of the Value Clarification Technique (VCT) on students' respect behavior. The method used in this research is quantitative, with an experimental research type using a true experimental, pre-test, and post-test Control Group Design. The data collection tool used a respect behavior questionnaire, and the sampling technique used simple random sampling. The population in this study consists of 148 students from the Islamic Guidance and Counseling Study Program at UIN Sayyid Ali Rahmatullah Tulungagung, with a sample of 60 students divided into two groups: an experimental group and a control group, each consisting of 30 students. The data analysis techniques used were the Wilcoxon test and the N-Gain score. The results showed a significant increase in respect behavior among students who received the VCT intervention, and the VCT technique was moderately effective in improving respect behavior.